Perpetuation of Psidium species through stooling and assessment of growth behaviour of clonal rootstocks under subtropical conditions - SAROJ, P L (The Indian Journal of Agricultural Sciences, 2012)
The investigation was carried out to standardize vegetative means of mass perpetuation of Psidium species through stooling technique and to assess growth behaviour of clonal rootstocks under subtropical conditions. The coppicing capacity among Psidium species varied with maximum number of desirable shoots/ plant in Psidium chinensis (27.33) and minimum in P. friedrichsthalianum (9.12). All the Psidium species under investigation, viz Psidium cujavillis, P. molle, P. chinensis and P. cattleianum except P. friedrichsthalianum can be successfully perpetuated by stooling with the combined treatment of IBA+NAA (7500 ppm). The rooting success varied between 9.53 and 100.00%, and field establishment of rooted shoots between 0.0-97.13%. The P. chinensis gave cent per cent rooting with 93.13% field establishment while P. friedrichsthalianum gave only 9.53 % rooting and no plants were established under field conditions. The remaining species, viz P. cujavillis, P. cattleianum and P. molle gave more than 91.69% rooting and more than 84.03% establishment of rooted shoots. The correlation between rooting versus biochemical and anatomical parameters revealed that higher phenol content and C:N ratio of stooled plants as well as more intercellular space and breadth of sclerenchymatous cells have better impact on rooting while higher protein and longer length of sclerenchymatous cells did not make any impact. Under uniform management, maximum plant height (106.90 cm) was obtained in P. cattleianum while minimum in P. chinensis (55.80 cm) after six months of transplanting. The stock girth was also maximum in P. cattleianum (3.91 cm), followed by P. molle (3.69 cm), P. cujavillis ( 3.32 cm) and minimum in P. chinensis (2.89 cm). The number of branches, intermodal length (cm), number of leaves / plant, average leaf area (cm2) and total leaf area / plant (cm2) also varied significantly. Based on initial growth behaviour, these Psidium species can be relatively categorized as dwarf (P. chinensis), semidwarf (P. molle) and vigourous species (P. cattleianum and P. cujavillis).